An Unusual Presentation of Extracavitary Primary Effusion Lymphoma: Internal Jugular Vein Occlusion, Intractable Symptoms of Intracranial Hypertension, and Prolonged Remission after Highly Active Antiretroviral Therapy - Ghosh, Anindita; Zvavanjanja, Rodrick Chitaurirwa; Baalwa, Joshua (Case Reports in Hematology, 2022)
Primary involvement of the skeletal muscle by extracavitary primary effusion lymphoma (PEL) is an extremely rare phenomenon. We report an unusual case of PEL involving the jugulodigastric skeletal muscle without serous cavity involvement which resulted in complete occlusion of the ipsilateral proximal internal jugular vein, causing the patient to present with clinical features of intractable throbbing headache, photophobia, acute confusion state, sporadic syncopal attacks, and dyspnea without obvious palpable neck swellings. This led to an initial clinical suspicion, dedicated diagnostic workup, and empiric therapy for acute meningoencephalitis, severe atypical pneumonia, and acute pulmonary embolism. Owing to his refractory symptoms, exploratory CT imaging eventually revealed a heterogenous jugulodigastric mass, and finally, a pathologic diagnosis of extracavitary PEL was identified as the cause of his intracranial hypertension. The patient remains in remission 22 months after commencing a dolutegravir-based HAART regimen without any chemotherapeutic intervention.